2014
DOI: 10.1111/hel.12119
|View full text |Cite
|
Sign up to set email alerts
|

IL10 Single Nucleotide Polymorphisms are Related to Upregulation of Constitutive IL‐10 Production and Susceptibility to Helicobacter pylori Infection

Abstract: Our results indicate that IL10 variants rs1800896, rs3024491, rs1878672, and rs3024496 are more consistently associated with the presence of anti-H. pylori IgG by inducing increased production of IL-10. Further studies are underway to elucidate the role of additional genetic variants and to investigate their impact on the occurrence of gastric cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 27 publications
1
14
0
5
Order By: Relevance
“…In another study, Eskdale et al (1998) suggested that a haplotype of IL-10 was associated with the highest overall IL-10 secretion, and that the levels of secreted IL-10 could vary in humans according to the genetic composition of the IL-10 locus. However, more recent reports have demonstrated elevated levels of IL-10 associated with promoter polymorphisms (Heiskanen et al, 2010;Assis et al, 2014).…”
Section: Discussionmentioning
confidence: 95%
“…In another study, Eskdale et al (1998) suggested that a haplotype of IL-10 was associated with the highest overall IL-10 secretion, and that the levels of secreted IL-10 could vary in humans according to the genetic composition of the IL-10 locus. However, more recent reports have demonstrated elevated levels of IL-10 associated with promoter polymorphisms (Heiskanen et al, 2010;Assis et al, 2014).…”
Section: Discussionmentioning
confidence: 95%
“…[12][13][14][15][16] Allele G of marker rs3024496 in IL10, which was found to be homozygous in the unaffected mother and heterozygous in the affected children, was reported to positively correlate with IL-10 concentrations in blood. 41 It is thus possible that this variant may contribute to protection from autoimmunity and intestinal inflammation in the mother, which warrants further investigation. Finally, while shared between the affected half-siblings (III.5, III.6) and their mother (II.6), a SNV located in FURIN may contribute to the observed clinical phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…While SNVs in TMC8 and GTF2H5 are associated with phenotypically unrelated diseases (epidermodysplasia verruciformis and trichothiodystrophy, respectively) and are thus unlikely to act as modifiers, mutations in IL10 and IL10RB are associated with early-onset IBD [12][13][14][15][16] and the observed variants in these genes may thus influence the susceptibility to IBD in the described kindred. Although all four variants in IL10 and IL10RB are common, allele G of marker rs3024496 in IL10 was reported to positively correlate with blood IL-10 concentrations 41 and was homozygous (GG) in the unaffected mother and heterozygous (AG) in the affected children. As such, it is possible that rs3024496 contributes to incomplete disease penetrance in the mother.…”
Section: Investigation Of Potential Genetic Modifiers Responsible Formentioning
confidence: 99%
“…14 Helicobacter pylori can lead to IL-10 upregulation as a way to suppress an efficient immune response, which then favors infection and parasite survival. 15 The gene encoding human IL-10 is located on chromosome 1. Two SNPs that are associated with low IL-10 production have been reported in the promoter region of this gene: a CeT base transition at position À819 and a CeA base transition at position À592.…”
Section: Introductionmentioning
confidence: 99%